Microbiological analysis and determination of antimicrobial traits of green banana (Musa spp.) and papaya (Carica papaya) - Jahan, Nusrat; Noor, Rashed; Munshi, Saurab Kishore (Stamford Journal of Microbiology, 2019)
Green banana (Musa spp.) and papaya (Carica papaya), which are commonly consumed as vegetables, are fruits with lots of health benefits. Due to their various medicinal applications, both the fruits are likely to contain antimicrobial properties. In this regard, present study was undertaken to determine the microbiological quality as well as the anti-bacterial traits of fresh green banana and papaya. To serve the purpose, a total of 12 samples (6 green bananas and 6 green papaya) were collected from different local and super shops as well from cultivation land of some villages of Bangladesh. The samples contained the microbial contamination with viable bacteria and fungi up to 107cfu/g and 103 cfu/g. Among the pathogenic bacteria, Staphylococcus spp. Pseudomonas spp. and Vibrio spp. were predominant as found in most of the samples in average of 102 cfu/g. Whereas Escherichia coli, Salmonella spp. and Shigella spp. were totally absent in all the samples. On the other hand, Klebsiella spp. was present in same samples. Additionally, the anti-bacterial poverties of the samples were chalked out. The in-vitro antimicrobial activities of the ethanolic, methanolic and hot water extracts of the samples were noticeably found against all the tested bacteria. Overall, present study revealed that both the green fruit samples were highly contaminated although they have antimicrobial activities. Thus, consumers’ awareness on the risk of consuming pathogen contaminated vegetables needs to be re-awakened and further investigations are required for potential antimicrobial properties. Stamford Journal of Microbiology, Vol.8(1) 2018: 41-45